Этнические процессы в Кавказской Албании в Период античности и в раннем средневековье - Акопян, Алексан (ՀՀ ԳԱԱ հրատ.)
Ք.ա. Դ–Գ դդ. յոյն հեղինակներին յանգող տեղեկութիւններում «աղուաններ» (ալբաններ, առանցիներ) անուանումը տրւում է Կուրի, Իորիի, Կովկասեան լեռների (մինչեւ Դերբենդի անցքը) եւ Կասպից ծովի միջեւ ընկած տարածքի բնակչութեանը։ Տարաժամանակեայ տուեալների համադրումը թոյլ է տալիս այդ անուան տակ տեսնել հիմնականում նախալեզգիական էթնոլեզուական ընդհանրութեան մասնատումից առաջ եկած ցեղերի մի խումբ։ In the first evidence on Albanian, which goes back to Greek authors of the IV-III centuries BC, the name “Albans” (Aluans, Arans) is given to the population inhabiting the territory between the downstream of Kur, Iory, Caucasian mountain ridge (untill Derbend) and Caspian Sea. The analysis of the data of different periods makes it possible to render this term primarily as a group of tribes, formed as a result of splitting up of the prelesgianethnolinguistic entity.
Keywords: История